LEGAL MEASURES ON PERSONAL WITNESS PROTECTION IN HUMAN TRAFFICKING CASE - Singha - assawarat, Chairoj (Journal of MCU Nakhondhat, 2020)
This article of this study were: 1) study the problem of legal measures on personal witness protection in human trafficking case. 2) study legal measures on personal witness protection in human trafficking case is foreign countries and Thailand. 3) analyze laws related to legal measures on personal witness protection in human trafficking case is foreign countries and Thailand. And 4) propose amendments to laws related to legal measures on personal witness protection in human trafficking case. This research was a qualitative research use study of documents and legal texts. The research results found that: 1) Problems with legal measures such as: 1.1) Limitations in the work of agencies involved in human trafficking; 1.2) participation in the human trafficking process, 1.3) non - cooperative victims of human trafficking, and 1.4) imitations on performance monitoring. 2) legal measures on personal witness protection such as: 2.1) Witness Protection Act in Criminal B.E. 2546, 2.2) Prevention and Suppression of Human Trafficking Act B.E. 2551 2.3) Human Trafficking Act B.E. 2559 2.4) Criminal 2.5) Criminal Procedure, and 2.6) Constitution of the Kingdom of Thailand B.E. 2560. 3) legal measures is foreign countries and Thailand such as: 3.1) reasons for witness protection in human trafficking cases, 3.2) process of providing witness protection in human trafficking cases, and 3.3) problems and barriers to preventing human trafficking in Thailand. And 4) guidelines for solving legal measures such as: addition of Human Trafficking Act B.E. 2551 Section 36. The protection of the safety of witnesses and family members in that country, and the increase in compensation and witness costs.